The Texts of St. Jerome, Sedulius Scottus and Beda Venerable in Plock and Mosan Biblical Manuscripts of the twelfth century. An attempt at comparison - Misiarczyk, Leszae (Saeculum Christianum. Pismo Historyczne, 2021)
This paper concerns the comparison of three twelfth-century biblical manuscripts from Plock, namely the so-called The Bible of Plock and The Evangeliary of Princess Anastasia with two Mosan biblical manuscripts: The Evangeliary of Averbode and the Biblia Universa transcribed in the same period. The first three texts: Beatissimo Papae Damaso (Novum opus), Prologus quatuor evangeliorum (Plures fuisse) and Iheronimus Damaso Pape (Sciendum etiam) – the last one is not included in the Bible of Plock - and Evangeliary of Princess Anastasia are of St. Jerome. In contrast, the introductions to the Synoptic Gospels: Argumentum secundum Matheum, Prologus in Marco and Prologus sancti Evangelii secundum Lucam are not the texts of St. Jerome, as is sometimes mistakenly repeated by different scholars, but were written by Sedulius Scottus, an Irish monk and a poet who lived and worked in a school in Leodium in the ninth century, whereas the introduction to the Gospel according to St. John: Prephatio in Evangelium secundum Iohannem was written by Bede the Venerable. While the texts of Jerome were quite commonly used in medieval biblical manuscripts, the fact that the introductions to the Synoptic Gospels are written by Sedulius Scottus and are present in both The Bible of Plock as well as partially in The Evangeliary of Princess Anastasia is a very strong argument for the Mosan origin of the twelfth century biblical manuscripts of Płock. The comparative analysis of the texts themselves clearly leads to several important conclusions. First, the Bible of Plock and Evangeliary of Princess Anastasia are closer to the version of the text preserved in the Biblia Universa, a codex written in the monastery of Sancti Trudonis, than to the Evangeliary of Averbode. It follows that the sources for the biblical manuscripts of Plock from the twelfth century should be searched at Mosan Benedictine monasteries, perhaps in the very monastery Sancti Trudonis near Liège. Second, the Gospel according to St. Mark generally follows the version of the text preserved in the Biblia Universa and the Bible of Plock but not all the time. It should therefore be hoped that the further comparative studies, especially of the version of the biblical text, will confirm this relationship and will help to determine whether the codex was written in the Meuse River region or is it a copy of the Bible of Plock made on the spot. Thirdly, and this is an extremely interesting proposal, the Evangeliary of Princess Anastasia, not counting minor changes made by a copyist like converting - tium to - cium, is very much dependent on the Bible of Plock. If, as it is confirmed by records of the miracles, the Bible was already in Plock in 1148 or before that date, it is very likely that the Evangeliary of Princess Anastasia, would be a copy of the text made on the spot in a local Plock scriptorium as a foundation of Boleslaw Kedzierzawy and a votive offering for the salvation of his deceased wife Anastasia. The codex would therefore arise after her death, dating back to the year 1158 in Plock in the time of Bishop Werner and would not have been brought by him following his trip to Aachen. These conclusions, for obvious reasons, are only preliminary, as comparison of the texts is not fully detailed and more comprehensive conclusions will be presented only after benchmarking a version of the biblical text of the four Gospels.